DEVELOPMENT OF ETHNO-CRT LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS AND SCIENCE LITERACY IN ECOLOGY AND BIODIVERSITY MATERIALS - Desandra Putri, Enjelina; Sudarmin, Sudarmin; Tri Prasetya, Agung (Universitas Negeri Semarang, 2025)
This research aims to develop an Ethno-CRT (Culturally Responsive Teaching) learning model based on Ethnoscience to improve students' critical thinking skills and science literacy on ecology and biodiversity materials. This research is a development research using a 4-D model (Define, Design, Develop, and Disseminate). The products developed include Ethno-CRT learning model books, syllabus, lesson plans, science e-modules, as well as critical thinking and science literacy test instruments. The results of validity by experts and readability by students show that the entire Ethno-CRT mitigation model is in the